Analysis of Beta-Carotene, Tocopherol and Fatty Acid in Red Palm Oil for Development as Soap Products - Meepun, Nipaporn; Noparat, Pongsak (Burapha Science Journal, 2024)
Background and Objectives : Palm oil is a type of oil that can be used as a source of fatty acids, which are cleaning agents produced from the reaction of fats with strong alkalis. Red palm oil is a crude palm oil obtained specifically from pressing the fruit's flesh and has not undergone bleaching. It has a balanced composition of saturated and unsaturated fatty acids and is rich in important nutrients. Therefore, the aim of this research is to analyze the amount levels of beta-carotene, tocopherols, and fatty acids in red palm oil obtained from pressing the pulp of fallen oil palm fruit, and to develop bar soap products from it. The results of this study can provide a pathway for generating income and increasing the value of palm oil products during periods when palm oil prices fluctuate according to market dynamics. Methodology : Red palm oil obtained from extraction was analyzed for beta-carotene and tocopherols using high-performance liquid chromatography techniques. The fatty acid content was analyzed using gas chromatography. The oil was then used to develop bar soap products. The resulting soap was tested for user satisfaction and evaluated for its physical characteristics and chemical properties. Main Results : The analysis of red palm oil found that the amount of beta-carotene and tocopherol was 60.89 and 21.67 mg/100g, respectively. The fatty acid content included lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, palmitoleic acid, linoleic acid, and linolenic acid, found at percentages of 0.25, 1.15, 39.11, 3.80, 0.36, 0.17, 9.96, and 0.35 by mass, respectively. User satisfaction testing regarding sensory characteristics, including foam quantity, skin cleansing ability, skin moisture, fragrance, color, and soap hardness, was conducted with 30 users. The results indicated that formulation C had the highest overall satisfaction score of 6.92. Physical testing showed a pH value of 9.76±0.02, an immediate foam volume of 27.00±2.00 mL after shaking, and corrosion percentage of 15.25±1.53. For the chemical properties, the insoluble matter in ethanol was found to be 1.92±0.35%, total fat matter content was 64.57±1.29%, and no free caustic alkali content was detected. Conclusions : Red palm oil is rich in beta-carotene, tocopherols, and both saturated and unsaturated fatty acids. When developed into soap products and assessed for their physical and chemical properties, they were found to meet the criteria of community product standards and industrial product standards. This ensures safety for use and serves as a pathway for generating income, adding value to palm oil.